Optimization of a Validated UV-Spectrophotometric Methodology for Assessment of Apigenin in Bulk Powder - Shetti, Priya; Jalalpure, Sunil S. (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: Apigenin (4,5,7 Trihydroxyflavone) is a natural compound of flavonoids class, which is found in various plant constituents. Since primitive years, Apigenin has been used as a traditional medicine, because it possesses biological functions. Common ayurvedic formulations comprising apigenin are in market. Hence quality control of preparation covering apigenin is desirable. Objectives: In present study, pointed to enhance and validate UV Spectrophotometric method to evaluation of apigenin in bulk powder. Methods: Using methanol as solvent, UV Spectrophotometric method was developed. Apigenin showed supreme absorbance wavelength at 267 nm. New technique enhanced and validated in terms parameters such Specificity, Discrimination, Linearity, Correctness, Ruggedness, Solution stability as per each ICH guidelines. Results: The detector response for apigenin was linear in the sure concentration range of 2μg/mL- 10μg/mL with correlation coefficient of 0.9995. Newly developed method was found to be specific, Selective linear, Precise, Rugged, reproducible for estimation of apigenin with %RSD values less than 2%. Conclusion: In this study Development and Validation of UV-Spectrophotometric method can be employed for the apigenin assessment in bulk powder.
Keywords: Apigenin; Absorbance; ICH guidelines; Ruggedness; Spectrophotometric; Ayurvedic Formulations